SYSTEM DYNAMICS MODELING OF CARBON CAPTURE STORAGE IMPLEMENTATION IN ULTRA-SUPERCRITICAL COAL-FIRED POWER PLANT: A CASE OF JAWA 7 CFPP - Reminton Helmi Aqil F., M
Coal-Fired Power Plant (CFPP) took 60% of Indonesia’s Energy Mix, reflecting a high dependency on coal to generate electricity. Along with the increasing amount of electricity demand, GHG emissions gradually arise as an impact of CFPP activities. However, the Government of Indonesia (GoI) has committed to reduce its carbon emissions based on Indonesia Nationally Determined Contribution (INDC) in the Paris Agreement. The emission reduction target is 29% with Indonesia’s efforts and 41% with international support by 2030. The implementation of Carbon Capture Storage (CCS) in Ultra-Supercritical (USC) CFPP is proposed to be one of the most suitable solutions for supporting INDC to reduce GHG emissions. Existing business issues derived from stakeholder interviews and literature reviews using system thinking as a qualitative approach resulting in determined key factors of the complex system in the electricity generation business. The results of qualitative approach are combined with quantitative approach using mathematical equations in system dynamics modeling. Several scenarios will be simulated to represent the actual condition and show the implication of how variables change over time within the implementation of CCS in USC CFPP in reducing GHG Emissions. The CCS implementation simulation resulted in reduced GHG emissions. The GoI plays a vital role in financial and regulatory support. However, the amount of reduced emission is not significant compared to CFPP phase-out program. Hence, the most effective scenario is CFPP phase-out program with 40% CFPP portion in Indonesia’s energy mix which successfully lowered the GHG emission to 5.63 billion tCO2e with an investment of 12.79 billion USD.